IDNLearn.com makes it easy to get reliable answers from knowledgeable individuals. Discover prompt and accurate answers from our community of experienced professionals.
Sagot :
Answer:
(2,5)
Step-by-step explanation:
y= 4x-3
y=-2x+9
-------------------------
4x-3=-2x+9
6x-3=9
6x=12
x=2
-----------------
y = 4(2)-3
y =8 -3
y=5
(2,5)
Answer:
1st box: 6x - 3 = 9
2nd box: 6x = 12
3rd box: x = 2
4th box: y = 4(2) - 3
5th box: y = 8 - 3
6th box: y = 5
Step-by-step explanation:
Part A-
1) 4x-3 = -2x+9
2) 4x+2x -3 = -2x+2x + 9
3) 6x -3 = 9
4) 6x -3+3 = 9+3
5) 6x = 12
6) 6x/6 = 12/6
7) x = 2
Part B-
1) y=4x-3
2) y=4(2)-3
3) y=8-3
4) y= 5
Therefore, x = 2 and y = 5.
Uh, I think I did this one… good luck ;p
We value your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. IDNLearn.com has the solutions you’re looking for. Thanks for visiting, and see you next time for more reliable information.